Lethal activity of BRD4 PROTAC degrader QCA570 against bladder cancer cells - Wang, Qiang; Li, Baohu; Zhang, Wenkai; Li, Zhuoyue; Jiang, Bo; Hou, Sichuan; Ma, Shumin; Qin, Chong (Frontiers in Chemistry, 2023)
Bladder cancer, the second most common malignancy worldwide of the urinary tract, remains a virtually intractable disease, and efforts to identify innovative and effective therapies are urgently needed. Recent studies have identified the BRD4 protein as an essential factor in regulation of proliferation and apoptosis of bladder cancer cells, and it shows promising potential for pharmacologic treatment against bladder cancer. In this study, we have evaluated the biological function of QCA570, a novel BET degrader, on multiple bladder cancer cells and explore its underlying mechanisms. QCA570 potently induces degradation of BRD4 protein at nanomolar concentrations, with a DC50 of 1 nM. It decreases EZH2 and C-MYC levels by transcriptional suppression and protein degradation. Moreover, the degrader shows antiproliferation activity with induction of cell apoptosis and cell cycle arrest of bladder cancer cells. These findings support the potential efficacy of QCA570 on bladder cancer.